Pengembangan Media Kartu Gambar Digital Untuk Meningkatkan Kemampuan Kognitif dan Rasa Cinta tanah Air Pada Pembelajaran IPS Siswa Kelas V di Sekolah Dasar - Jofi Ardiansa; Wahyu Sukartiningsih; Waspodo Tjipto Subroto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Social studies learning for fifth graders at SDN 3 Soko Lamongan tends to like a lot of things that remember and understand the social studies material presented. Innovative and effective learning media are needed to attract and assist students in improving cognitive abilities and a sense of patriotism. Based on this, this study aims to describe love and differences in cognitive abilities and a sense of homeland before and before using digital picture card media. This study uses research and development methods or Education Research and Development (RnD) and trial learning outcomes using pre-test and post-test. The study was conducted in the 2021/2022 academic year with 20 students as research subjects, and data collection techniques used namely observation, interviews, expert validation, student response questionnaires and learning outcomes acquisition tests. The results of the validation research on learning media have adequate validity and feasibility. The results of the media experts obtained a validity percentage of 89%, the results of the material content experts obtained an overall validity percentage of 86%, the assessment results from the fifth grade teacher or material content experts obtained a 90% validity percentage and the results of the responses or responses of students in the field achieved the overall validity percentage. 89%. Meanwhile, the students' cognitive ability pretest test got an average score of 59 while the posttest got an average score of 86.5. In the affective domain, students get an average score of 61 while the posttest gets an average score of 87. Thus, it can be said that digital picture cards can improve cognitive abilities and love for the homeland of fifth grade students.